Hubungan Marketing Mix dan Hospital Brand Image dengan Minat Kunjungan Ulang Pasien di RSI Sultan Agung Banjarbaru - Fitriani, Fitriani; Ifansyah, M. Noor; Zubaidah, Zubaidah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Hospitals are required to provide high-quality services to increase patient visits. Over the past six months, RSI Sultan Agung Banjarbaru has experienced a decline in the number of patient visits. This study aimed to analyze the relationship between the marketing mix and hospital brand image with revisit intention. The study employed a correlational analytic design, involving an outpatient population of 107,146 patients. A total of 100 respondents were selected using purposive sampling, and data were collected through questionnaires. Data analysis was conducted using the Spearman’s Rho test. The results showed that the marketing mix and hospital brand image variables were both categorized as good, with percentages of 76% and 74%, respectively. Meanwhile, respondents’ revisit intention was categorized as interested, with a percentage of 97%. The Spearman’s Rho test showed no significant relationship between the marketing mix and revisit intention (p-value = 0.704), whereas hospital brand image had a statistically significant but weak relationship with revisit intention (p-value = 0.004). It can be concluded that revisit intention is not influenced by the marketing mix but is associated with hospital brand image. Therefore, hospitals are recommended to optimize other factors such as loyalty, satisfaction, brand equity, service quality, and patient experience to enhance revisit intention.